Assessment of film forming potential of Cordia dichotoma fruit mucilage (Boraginaceae): Alfuzosin hydrochloride as a drug of choice - Lohithasu Duppala, Sarada Anepu, Hema Naga Durga Divvela, Rajya Lakshmi Teku (Journal of Applied Pharmaceutical Science, 2016)
The objective of this present study was to develop and evaluate transdermal films of alfuzosin hydrochloride for controlled release at a predetermined rate over a prolonged period of time and assessment of film forming ability Cordia dichotoma fruit mucilage using alfuzosin as drug of choice. The films of alfuzosin were prepared by solvent evaporation technique. The formulations, from F1 to F3 contain Cordia dichotoma fruit mucilage (CDFM; 8%, 12% and 16%) and the formulations, from F4 to F6 contain CDFM along with sodium alginate (125 mg, 150 mg and 175 mg). Glycerin and propylene glycol were used as plasticizer; span-80 used as permeation enhancer; methyl paraben and propyl paraben were used as preservatives (in case of plant mucilage as polymer) in all the formulations. Fourier transform infra red spectral analysis studies showed that there is no drug polymer incompatibility. The films of alfuzosin were prepared by using different polymers such as C. dichotoma and also in combination with sodium alginate that had shown good results for all the evaluated parameters within the range. In vitro drug release studies had shown that the maximum release of drug was observed for F3 formulation was 91.87 ± 1.34 at 24 hrs and F6 formulation was 99.62 ± 0.14 at 24 hrs. The concentration of CDFM is increased from 8% to 16% that leads to enhancement of dissolution rate. In-vitro drug release studies of optimized formulations, F3 formulation followed first order and F6 formulation followed zero order kinetics. The obtained results were concluded that CDFM have good film forming ability alone and combination with sodium alginate.
Keywords: Alfuzosin hydrochloride, Cordia dichotoma fruit mucilage and Transdermal films.